A Cross-Sectional Multicenter Study of Workplace Violence against Prehospital Emergency Medical Technicians. (4th April 2018) - Hosseinikia, Seyed Hamid; Zarei, Shekufeh; Najafi Kalyani, Majid; Tahamtan, Sepideh
Abstract : Background and Purpose. Workplace violence is a global phenomenon and violation of human rights affects the people's self-esteem and quality of work and causes inequality, discrimination, disorder, and conflict at work. The present study was carried out aiming at determining the workplace violence against the prehospital emergency medical technicians (PEMTs) in three provinces of Fars, Kohgiluyeh and Boyer-Ahmad, and Bushehr, Iran. Materials and Methods. This was a cross-sectional multicenter study in which 206 PEMTs from Fars, Bushehr, and Kohgiluyeh and Boyer-Ahmad provinces participated. Simple random sampling was used in this study. In order to collect data, a researcher-made tool was used. Descriptive statistics and SPSS® software version 22 were used to analyze the data. Results. Among various types of workplace violence, the most frequent ones were verbal violence (78.1%), physical violence (60.3%), and cultural violence (31.7%), respectively. The most important factor in the occurrence of workplace violence was the lack of the awareness of people about the duties of the PEMTs. With regard to the handling of the violent situations, the results indicated that 61.6% of the personnel asked the attacker to calm down. 48.5% of PEMTs believed that violence was normal in their work. Conclusion. Due to the high rate of workplace violence against PEMTs, it is suggested that methods such as formal training and retraining programs for the employees, general education with regard to the duties of the PEMTs, and socially supporting them should be used to reduce and control violence.